Analisis Penerapan Metode EOQ dalam Pengelolaan Manajemen Persediaan (Studi Kasus pada Royal Folding Gate cabang Jatinangor) - Purba, Rivan Salvador; Rivani, Rivani (Forum Bisnis Kewirausahaan, 2025)
Royal Folding Gate, a business in the manufacturing sector, faces challenges in inventory management at its Jatinangor branch, where suboptimal stock management methods lead to inventory accumulation and high costs. This study aims to identify inventory management challenges and analyze the impact of implementing the Economic Order Quantity (EOQ) method on the operational efficiency of Royal Folding Gate. The research methodology employs a descriptive qualitative approach, utilizing primary and secondary data. The analysis results show that the implementation of the EOQ method at Royal Folding Gate can reduce storage costs per unit by a total of up to Rp1,835,477. The EOQ calculation provides an optimal order quantity, reduces the frequency of inefficient ordering, and prevents overstock and stockout situations. This study demonstrates that the EOQ method is an effective solution for managing inventory, reducing costs, and improving operational efficiency at the Jatinangor branch of Royal Folding Gate.